2008
DOI: 10.1097/fbp.0b013e3282fe8849
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of morphine withdrawal signs by muscimol in the locus coeruleus of rats

Abstract: This study examined the effects of intra-locus coeruleus injection of a gamma-amino-butyric acid type A (GABAA) receptor agonist on naloxone-induced withdrawal signs of morphine-dependent rats. Twenty different withdrawal signs were assessed. The total withdrawal score was calculated and used as an index of withdrawal intensity. The gamma-amino-butyric acid agonist and antagonists were injected 15 and 30 min before naloxone injection, respectively. Muscimol, a GABAA agonist (25, 50, and 100 ng/site), decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Others have demonstrated that non-selective pharmacological inactivation or lesions to the LC lessen morphine withdrawal symptoms, prevent footshock-evoked c-fos expression throughout the brain, and disrupt both unconditioned and conditioned aversive responses (Mirzaii-Dizgah et al, 2008; Neophytou et al, 2001; Passerin et al, 2000), but it has previously been untenable to selectively inhibit the activity of only these NE neurons and assess their role in stress-induced behaviors. To examine the role of LC-NE neurons in stress-induced anxiety-like behavior, we implemented a restraint stress paradigm, immediately followed by anxiety testing in the open field test (OFT) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Others have demonstrated that non-selective pharmacological inactivation or lesions to the LC lessen morphine withdrawal symptoms, prevent footshock-evoked c-fos expression throughout the brain, and disrupt both unconditioned and conditioned aversive responses (Mirzaii-Dizgah et al, 2008; Neophytou et al, 2001; Passerin et al, 2000), but it has previously been untenable to selectively inhibit the activity of only these NE neurons and assess their role in stress-induced behaviors. To examine the role of LC-NE neurons in stress-induced anxiety-like behavior, we implemented a restraint stress paradigm, immediately followed by anxiety testing in the open field test (OFT) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, various receptors and signaling molecules in the LC were demonstrated to be involved in the precipitation of withdrawal's somatic signs. Examples include alpha-2 adrenoceptors (Aghajanian, 1982; Engberg et al, 1982), GABA-A receptor (Mirzaii-Dizgah et al, 2008), glutamate transporters (Ozawa et al, 2004; Nakagawa and Satoh, 2004), and the cAMP pathway, including adenylyl cyclases 1 and 8 and cAMP response element-binding protein (Valverde et al, 2004; Oh et al, 2007; Zachariou et al, 2008; Han et al, 2006; Lane-Ladd et al, 1997). However, the role of the LC in the precipitation of somatic withdrawal signs remains somewhat debatable, given that lesioning of noradrenergic terminals arising from the LC does not inhibit the precipitation of physical symptoms of opioid withdrawal (Chieng and Christie, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results of our study, administration of a GABA B agonist into the LC was shown to decrease withdrawal symptoms, while administration of a GABA B antagonist did not lead to any behavioural changes. Although microinjection of the GABA A agonist muscimol into the LC dose-dependently decreased withdrawal symptoms, GABA A and GABA B antagonists were reported to have no effect [26]. In some of the studies showing an effective suppressive action of drugs on morphine withdrawal, jumping behaviour was found to be affected in different ways - that is, increased [27], decreased [28] or not changed at all [29].…”
Section: Discussionmentioning
confidence: 99%